2017
DOI: 10.2147/ndt.s153505
|View full text |Cite
|
Sign up to set email alerts
|

Altered emotional prosody processing in patients with Parkinson’s disease after subthalamic nucleus stimulation

Abstract: BackgroundPatients with Parkinson’s disease (PD) exhibit deficits in recognizing and expressing vocal emotional prosody. The aim of this study was to explore emotional prosody processing in patients with PD shortly after subthalamic nucleus (STN) deep brain stimulation (DBS).MethodsTwo groups of patients with PD (pre-DBS and post-DBS) and one healthy control (HC) group were recruited as participants. All participants (PD and HC) were assessed using the Montreal Affective Voices database 50 Voices Recognition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We observed an effect of DBS on emotional prosody recognition at the subgroup level, and we can assume that studies suggesting that there is no post-DBS effect are those that fail to take motor lateralization at disease onset into account, thereby inducing a noneffect. For instance, a recent study concluded that after STN DBS, the ability to recognize emotional prosody remains intact, and only fear production is impaired (Jin et al, 2017). It is interesting to note that its results at the whole group level were almost the same as ours (compare Supplementary Material Fig.…”
Section: Differential Impact Of Stn Dbs According To Motor Symptom Asymmetrysupporting
confidence: 77%
See 1 more Smart Citation
“…We observed an effect of DBS on emotional prosody recognition at the subgroup level, and we can assume that studies suggesting that there is no post-DBS effect are those that fail to take motor lateralization at disease onset into account, thereby inducing a noneffect. For instance, a recent study concluded that after STN DBS, the ability to recognize emotional prosody remains intact, and only fear production is impaired (Jin et al, 2017). It is interesting to note that its results at the whole group level were almost the same as ours (compare Supplementary Material Fig.…”
Section: Differential Impact Of Stn Dbs According To Motor Symptom Asymmetrysupporting
confidence: 77%
“…SI 2 in this article with Fig. 1b in Jin et al, 2017). Had these authors analyzed their data separately according to motor lateralization, we can speculate that the patterns of results would have been different.…”
Section: Differential Impact Of Stn Dbs According To Motor Symptom Asymmetrymentioning
confidence: 78%
“…The fourth aim was to provide the first meta-analytic assessment of whether DBS is linked to greater social perceptual impairment. DBS is an established alternative option for reducing motor symptoms for PwPD who fail to respond to, or are not suitable for, dopaminergic treatment (Biseul et al, 2005;Dujardin et al, 2004b;Jin et al, 2017). The subthalamic nucleus can be functionally divided into sensorimotor (dorsolateral), limbic (medial) and cognitive (ventromedial) regions.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Importantly, STN-DBS also affects vocal expression by improving the oral motor control of PD patients' speech [60]. Although in parallel, it could negatively impact their expression and decoding of emotions [61,62]. These effects would depend on the exact location of the electrode's implantation in the STN (e.g.…”
Section: Discussionmentioning
confidence: 99%